2020
DOI: 10.21037/atm.2020.04.58
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis of plasma protein in patients with neuropsychiatric systemic lupus erythematosus

Abstract: Background: The aim of this study was to evaluate serum biomarkers of systemic lupus erythematous (SLE) patients, with and without neuropsychiatric (NP) manifestation by high-resolution proteomic analysis.Methods: SLE patients with NP (NPSLE, n=9), SLE patients without NP (non-NPSLE, n=9) and healthy controls (HC, n=9) were prospectively enrolled in this study, and their plasma samples were collected and pooled into 3 NPSLE, 3 non-NPSLE and 3 HC samples for discovery profile. The TMT-LC-MS/MSbased proteomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Previous studies have observed abnormal alterations in many mRNAs, proteins and metabolites in SLE patients. For example, elevated expression of CTRP3 and TRYP2, which might participate in the pathogenesis, were observed in plasma from neuropsychiatric SLE ( 21 ). Additionally, serum properdin, collectin-11 and thrombospondin-4 levels were able to monitoring the diseases activity of SLE patients ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed abnormal alterations in many mRNAs, proteins and metabolites in SLE patients. For example, elevated expression of CTRP3 and TRYP2, which might participate in the pathogenesis, were observed in plasma from neuropsychiatric SLE ( 21 ). Additionally, serum properdin, collectin-11 and thrombospondin-4 levels were able to monitoring the diseases activity of SLE patients ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…201 More than 200 proteins have been identified as potential biomarkers, some of them for SLE patients in general, but others for specific organs involved like LN or NPSLE. 202204…”
Section: Biomarkers In Neuropsychiatric Slementioning
confidence: 99%
“…A growing number of researchers are turning to proteomics as a supply of novel biomarkers for a variety of disorders. Quantitative proteomics methods based on tandem mass tags (TMT) have been extensively employed to date for protein biomarker research and the assessment of protein modification in several autoimmune diseases and malignancies ( 26 ). The activation and control of inflammatory responses, as well as tissue homeostasis, are all mediated by macrophages.…”
Section: Introductionmentioning
confidence: 99%